REINVENTING KONSEP DIRI DAN MOTIVASI BERPRESTASI DALAM MENCIPTAKAN PRESTASI BELAJAR SISWA - Asiyah Asiyah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
This article  is motivated by a phenomenon in the  achievement of student achievement that shows that  the  impulse to achieve the  feat of learning  in students is still low. Many things  that  have  a positive  and significant correlation of student learning achievement associated with them  is the concept of self-esteem and achievement motivation of students. View of education experts about  increasing and  decreasing the learning achievement of individuals can be influenced by the concept of self and motivation of its (Garg, Melanson  and Levin, 2007; Marjoribanks,  2003, Hill, Castellino, Lansford, Nowlin, Dodge, and Bates, 2004). The purpose of this paper  is to describe the self-concept and achievement motivation and student achievement.